2016
DOI: 10.1016/j.appet.2016.01.026
|View full text |Cite
|
Sign up to set email alerts
|

The relation between child feeding problems as measured by parental report and mealtime behavior observation: A pilot study

Abstract: Because feeding problems have clear negative consequences for both child and caretakers, early diagnosis and intervention are important. Parent-report questionnaires can contribute to early identification, because they are efficient and typically offer a 'holistic' perspective of the child's eating in different contexts. In this pilot study, we aim to explore the concurrent validity of a short screening instrument (the SEP, which is the Dutch MCH-FS) in one of its target populations (a group of premature child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 42 publications
4
17
0
1
Order By: Relevance
“…Interestingly, there were no significant relationships between parental report of feeding problems and observations of maternal emotional expression or sensitivity in mealtime interactions. This reflects a similar pattern of relationships between the MCHFS and observations of infant but not parent behaviour in a previous pilot study (Van Dijk et al, 2016).…”
Section: Accepted Manuscriptsupporting
confidence: 83%
See 2 more Smart Citations
“…Interestingly, there were no significant relationships between parental report of feeding problems and observations of maternal emotional expression or sensitivity in mealtime interactions. This reflects a similar pattern of relationships between the MCHFS and observations of infant but not parent behaviour in a previous pilot study (Van Dijk et al, 2016).…”
Section: Accepted Manuscriptsupporting
confidence: 83%
“…Finally, it is also vital to examine observations of parent-child interaction at a mealtime in addition to parental reports of feeding and eating behaviour. One pilot study has evaluated the relationship between the Dutch version of the MCHFS and observations of mealtimes with 29 prematurely born 9-18 month olds (Van Dijk et al, 2016). In this study, MCHFS scores were related to observed food refusal and feeding autonomy but did not relate to parental negative affect or mealtime instructions.…”
Section: The Montreal Children's Hospital Feeding Scalementioning
confidence: 91%
See 1 more Smart Citation
“…Los prematuros fueron quienes tenían más probabilidades de ser diagnosticados, probablemente debido a problemas neurológicos, como consecuencia de la alimentación mediante sonda naso u orogástrica y de las características de la relación temprana madre-hijo (Hvelplund, Hansen, Vinkel-Koch, Andersson, & Skovgaard, 2016). En una investigación reciente conducida en niños prematuros (Van Dijk, Bruinsma, & Hauser, 2016), hallaron que a medida que los padres informaban mayores problemas en la alimentación, los niños observados rechazaban en mayor medida los alimentos y comían de manera menos eficiente e independiente. Los niños prematuros de este estudio presenta-ron puntajes que indicaban ausencia de problemas en la alimentación o problemas leves.…”
Section: Introductionunclassified
“…Despite variation on the definition of problematic eating behaviours, these include food refusal (of certain types of foods), food fussiness or pickiness (refusal of new and familiar foods, accepting only a narrow range of foods), refusal of new foods (neophobia), grumpiness during mealtime and inadequate self-feeding skills [1,3,4]. The prevalence of these eating behaviours may vary between 7 and 65% [4,5].…”
Section: Introductionmentioning
confidence: 99%